PENGARUH TEKNIK PEMODELAN TERHADAP KETERAMPILAN MENULIS TEKS CERITA ULANG BIOGRAFI SISWA KELAS X SMA NEGERI 5 BUKITTINGGI - Wulandari, Sepria; Asri, Yasnur; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACT The aim of this article is to describe influences in using modeling technique toward student’s ability in writing biography text in X SMA Negeri 5 Bukittinggi. This research is quantitative research through experimental method. The result of the research are first,the ability of students of second grade in SMA Negeri 5 Bukittinggi in writing the text before using modeling technique in the stage of More than fair qualification (C) on avarage 65,59; second, the ability in writing the text after using modeling technique in the stage of good qualification (B) on avarage 78,36; third, the ability in writing the text has been used this method more effective than before use it. Kata Kunci: pengaruh, teknik pemodelan, teks cerita ulang biografi.